2017
DOI: 10.1002/2017gl075110
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Elastic Modulus of Snow

Abstract: The elastic modulus is the most fundamental mechanical property of snow. However, literature values scatter by orders of magnitude and hitherto no cross-validated measurements exists. To this end, we employ P wave propagation experiments under controlled laboratory conditions on decimeter-sized snow specimen, prepared from artificial snow and subjected to isothermal sintering, to cover a considerable range of densities (170-370 kg m −3). The P wave modulus was estimated from wave propagation speeds in transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 42 publications
5
66
0
Order By: Relevance
“…Hence, the single fibers should be viewed as small discrete snow cells. The elastic modulus E = 19 MPa we used for the FBM simulations is in agreement with the reported literature values (Gerling et al, 2017). In addition, the measurement method has a strong influence on the reported values.…”
Section: Model Calibrationsupporting
confidence: 88%
See 2 more Smart Citations
“…Hence, the single fibers should be viewed as small discrete snow cells. The elastic modulus E = 19 MPa we used for the FBM simulations is in agreement with the reported literature values (Gerling et al, 2017). In addition, the measurement method has a strong influence on the reported values.…”
Section: Model Calibrationsupporting
confidence: 88%
“…The method providing best results for the elastic properties of snow is based on measuring the propagation speed of acoustic waves, which induce deformations that are small and fast enough to be in the elastic range (Capelli et al, 2016). Gerling et al (2017) reported values of the elastic modulus in the range of 10-20 MPa for the density range of the weak layers of our samples (~170 kg/m 3 ). The elastic modulus E = 19 MPa we used for the FBM simulations is in agreement with the reported literature values (Gerling et al, 2017).…”
Section: Model Calibrationmentioning
confidence: 91%
See 1 more Smart Citation
“…In the prefailure stage, the elastic properties of snow have been subject to numerous experimental investigations (Gerling et al, ; Mellor, ; Narita, ) and were shown to be controlled by density as well as microstructural anisotropy. Failure of snow is generally considered to be governed by the Mohr‐Coulomb criterion (Chiaia et al, ; Fyffe & Zaiser, ; Gaume et al, ; McClung, ), where the shear strength increases linearly with the normal load.…”
Section: Introductionmentioning
confidence: 99%
“…Our assumption is justifiable, since the formation of initial bonds between ice crystals in snow takes place almost immediately [29,30]. The further increase of bond strength in snow (resulting in an increase of strength and elastic modulus) occurs at a time scale beyond the time scale of the failure process we consider in the model [31,32].…”
Section: A Sinteringmentioning
confidence: 99%